Modern Sports: Sponsorship, Betting, and Fiqh Ethics - Sulham Efendi Hasibuan; Nur Alia Harahap; Suci Pitriani Siregar; Annisa Barutu; Puji Maharani Harahap (CV. AULIANTECH, 2026)
Modern sports have transformed into a global industry involving massive capital turnover through sponsorship and broadcasting rights. However, this evolution has also raised ethical challenges concerning betting practices (maysir). This article aims to analyze the phenomenon of modern sports through the lens of Fiqh ethics, focusing on the legitimacy of sponsorship contracts, the legal status of betting, and the implementation of muamalah principles in maintaining the integrity of sports. The methodology employed is qualitative research with a library research approach, referencing the resolutions of the Majmaʿ al-Fiqh al-Islāmī and the fatwas of the Indonesian Ulema Council (MUI). The findings indicate that sponsorship is permissible as long as the promoted object does not contradict Sharia (i.e., not involving alcohol, gambling, or usury). Meanwhile, sports betting is categorized as strictly forbidden (haram) gambling because it contains elements of speculation (gharar) and the risk of material loss for participants. This article also formulates the parameters distinguishing between betting and prize-based competitions (ju’alah), where prizes must originate from a third party and be based on physical skill rather than luck. In conclusion, the application of Fiqh ethics in modern sports is crucial to ensuring that the industry's financial progress remains aligned with the objectives of Maqāṣid al-Sharīʿah, namely preserving the moral and spiritual welfare of the community.